LEGALITAS DAN LEGITIMASI LEMBAGA INTERNASIONAL DALAM INTERVENSI KEMANUSIAAN: NATO DI LIBYA - Wandi Abbas; Asma Amin; Sriwiyata Ismail (Jurnal Hukum Unsulbar, 2023)
Various issues in the arena of international relations often become debated and controversial. Both in terms of policies in maintaining world peace and security. One of the controversial things is in terms of the role and involvement of the state and international institutions in resolving a conflict in another country. Does the involvement of these actors solve problems and can resolve conflicts that occur or the involvement of third parties actually makes the situation and conditions in conflict countries worse. This is of course a concern considering that the motive for the involvement of the state and international institutions sometimes favors personal interests.